2016
DOI: 10.3389/fphar.2016.00217
|View full text |Cite
|
Sign up to set email alerts
|

A Ribonuclease Isolated from Wild Ganoderma Lucidum Suppressed Autophagy and Triggered Apoptosis in Colorectal Cancer Cells

Abstract: The mushroom Ganoderma lucidum (G. lucidum) has been consumed in China as a medicine for promoting health and longevity for thousands of years. Due to its paramount and multiple pharmaceutical effects, G. lucidum has received considerable attention from researchers and its chemical constituents as well as their respective functions were gradually unveiled by using modern research methods. Herein, we reported the isolation of a protein (Ganoderma lucidum ribonuclease, GLR) with anti-colorectal cancer activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…G. lucidum ribonuclease was detected to suppress cell autophagy in colorectal cancer cells. 34 On the contrary, the methanolic extract of G. lucidum induces autophagy of gastric adenocarcinoma cells. 34 In this study, we found that BSGLWE induced autophagosome formation by the results of TEM, Western blot and immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G. lucidum ribonuclease was detected to suppress cell autophagy in colorectal cancer cells. 34 On the contrary, the methanolic extract of G. lucidum induces autophagy of gastric adenocarcinoma cells. 34 In this study, we found that BSGLWE induced autophagosome formation by the results of TEM, Western blot and immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…34 On the contrary, the methanolic extract of G. lucidum induces autophagy of gastric adenocarcinoma cells. 34 In this study, we found that BSGLWE induced autophagosome formation by the results of TEM, Western blot and immunofluorescence. The formation of autophagosome is only one aspect of assessing autophagy activity, and degradation of autophagy substrates needs to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies strongly support the relevance of the interplay between autophagy and apoptosis. [22][23][24] Our result discovered that inhibition of autophagy via 3-MA increased the proportion of apoptotic 95D-Nrf2 cells, meaning that autophagy may potentially involve in Nrf2-associated activities in NSCLC. Then we detected changes of autophagy biomarkers in Nrf2 upregulated or downregulated cell lines, and these autophagy biomarkers dramatically changes in Nrf2 upregulated or downregulated cell lines.…”
Section: Discussionmentioning
confidence: 64%
“…Apoptosis induction has been demonstrated in cancer cells cultured with peptides isolated from edible mushrooms (Patel & Goyal 2012 ; Dan et al. 2016 ). Due to its safety as a traditional food and its potential therapeutic effects, Lentinus squarrosulus Mont.…”
Section: Introductionmentioning
confidence: 99%